Generational transformation in academic life in Iran - Mohammadi, Zahra (Opción, 2019)
This is a qualitative study of the generational transformations of academics in the last fifty years and their causes and consequences. The research methodology was based on grounded theory. The samples were selected purposively from professors of three comprehensive universities in Iran. The data were saturated with 52 exploratory interviews and analyzed using the ATLAS.ti software. Findings showed that morality and compliance with academic norms are moving toward corporatism and promotion. It was concluded that despite similarities among the three generations, the academic lifestyle of academics has changed, and elitist universities are moving towards populist and research-oriented entrepreneurial universities